Formation and Development of Character Education through the Simpatika Model - Pohan, Selamat (Yayasan Rahmat Islamiyah, 2025)
Character education is an important foundation in developing students with integrity and noble character. This article discusses the formation and development of character education through the Simpatika Model, an approach that emphasizes empathy, dialogic communication, and active participation in the learning process. This model was developed to create a learning environment conducive to the internalization of character values such as responsibility, honesty, cooperation, and social concern. The research was conducted using a qualitative approach through literature review and limited observations. The results indicate that the implementation of the Simpatika Model encourages emotional and social engagement in students and strengthens synergy between schools, families, and the community. This model is relevant for implementation as a holistic and sustainable character education strategy. This research recommends broader implementation of the Simpatika Model through teacher training, strengthening the role of teachers, and developing educational policies that support character values.